The Relationship between EFL Students’ Critical Thinking and Their Reading Comprehension - Salsabilla Kharisma Dewi; Ati Ningsih, Nuri; Kurniawan, Arri (Papanda Publisher, 2025)
Students often face challenges in reading comprehension, such as distinguishing main ideas and supporting details, connecting topics and background knowledge in the text, and concluding the contents of the reading. Therefore, it is important to investigate whether there is a relationship between students’ critical thinking ability and their reading comprehension performance. Using a quantitative correlational research design, the research involved 25 eleventh-grade students from SMAN 1 Jiwan, selected through cluster random sampling. To measure the ability of both variables, the critical thinking instrument used was the critical thinking questionnaire by Jie et al., while the reading comprehension instrument was a collection of validated questions that are arranged based on learning objectives in the classroom. The results showed the not statistically significant relationship between critical thinking and reading comprehension (sig. 0.184), although there was a tendency for a weak positive correlation (r = 0.274). This may be due to an imbalance between critical thinking and reading comprehension skills, limited language and basic linguistic skills, and a lack of practice in applying critical thinking in reading. Therefore, the application of critical thinking in reading comprehension activities is needed, and the development of students' language skills is needed in EFL learning.